UJI EFEKTIFITAS LARVISIDA INFUSA KULIT BUAH MANGGIS (Garcinia mangostana L) TERHADAP LARVA NYAMUK Culex quinquefasciatus - , NATHINA FINIASANA WIDIARTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background. Elephantiasis has become epidemic in tropical countries. This disease transmitted through mosquito bite, mainly by Culex quinquefasciatus. Mangosteen skin is expected to have larvicidal effect such as alpha-mangostin. Objective. To determine the potent larvicidal activity (LC50 and LC90) of Garcinia mangostana L infusion